2010
DOI: 10.1016/j.bpa.2009.09.010
|View full text |Cite
|
Sign up to set email alerts
|

New insights into acute coagulopathy in trauma patients

Abstract: Abnormal coagulation parameters can be found in 25% of trauma patients with major injuries. Furthermore, trauma patients presenting with coagulopathy on admission have worse clinical outcome. Tissue trauma and systemic hypoperfusion appear to be the primary factors responsible for the development of acute traumatic coagulopathy immediately after injury. As a result of overt activation of the protein C pathway, the acute traumatic coagulopathy is characterised by coagulopathy in conjunction with hyperfibrinolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 103 publications
0
40
0
1
Order By: Relevance
“…Clotting factor activity and platelet aggregation may be reduced by hypothermia (<33-34 °C). [11,23] White et al [24] found that acidosis may reduce the activity of the factor Xa/Va complex, and the activity will be persistently reduced by the increasing acidosis severity. NEUT% values were significantly increased in group 4, implying that group 4 had inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clotting factor activity and platelet aggregation may be reduced by hypothermia (<33-34 °C). [11,23] White et al [24] found that acidosis may reduce the activity of the factor Xa/Va complex, and the activity will be persistently reduced by the increasing acidosis severity. NEUT% values were significantly increased in group 4, implying that group 4 had inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue factor, the thrombin-thrombomodulin protein C pathway, endothelium, complement proteins, proinfl ammatory cytokines, and platelets play important roles in this interaction between inflammation and coagulation. [23,[25][26][27] The inflammation cytokines enhance endothelial expression/release of thrombomodulin resulting in enhanced activation of PC. [28] With increasingly severe trauma, the excessive increases in plasma catecholamine increase the release of tPA and PC, and the excessive consumption of coagulation factors and platelets, resulting in predominant hypocoagulability.…”
Section: Discussionmentioning
confidence: 99%
“…Patients suffering from major trauma often turn into a hypercoagulable state, which then frequently leads to pathological thrombosis [15]. Abnormal coagulation parameters can be found in 25% of trauma patients with major injuries [16]. Previous studies in trauma patients were able to highlight a significant and persistent increase in markers of thrombin generation and action, such as F1 þ 2 and TAT [17].…”
Section: Introductionmentioning
confidence: 99%
“…Beside the discussion about the substitution of coagulation factors and blood components, there is evolving knowledge that trauma itself has time-or incident-depending effects on coagulation [14]. Initially the combination of traumatic injury and tissue hypoperfusion results in a coagulopathy associated with a reduction in protein C levels.…”
Section: Key Parameters and Assessment Of Trauma-induced Coagulopathymentioning
confidence: 99%
“…A further anticoagulant activity is exerted by the de-activation of plasminogen activator inhibitor (PAI-1), resulting in enhanced fibrinolysis [16]. In addition to its anticoagulatory effects, protein C proteolytically activates the cell surface receptor protease-activated receptor-1 (PAR-1) and thus generates several cytoprotective effects by increasing the anti-inflammatory properties, anti-apoptotic activity, and protective function of the endothelial barrier , all being required for survival in acute shock [14]. Taken together, early post-…”
Section: Key Parameters and Assessment Of Trauma-induced Coagulopathymentioning
confidence: 99%